PROPERTIES OF UNFIRED COMPRESSED BRICKS USING CASSAVA WASTEWATER - Fetra Venny Riza; Ardiansyah Ardiansyah; Josef Hadipramana (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
This study was conducted to evaluate the performance of unfired compressed bricks (UCB) using the Indonesian National Standard SNI 15-2094-2000 as a reference. The tests included compressive strength, water absorption, salt content, density, and visual appearance. The bricks were produced by utilizing cassava wastewater, with cement and lime used as binding agents, mixed with red soil, galong soil, and sand, without undergoing a firing process. Variations in the composition of binder, soil, sand, and cassava wastewater were prepared with a ratio of 1:8:2 using 350 ml of wastewater. The specimens were molded using a steel mold with dimensions of 20 cm × 10 cm × 6 cm. Each mixture consisted of eight specimens and was cured for 28 days. The compressive strength of unfired bricks using cassava wastewater reached 6.39 MPa, while the control unfired bricks achieved 7.29 MPa. The average compressive strength of unfired bricks incorporating cassava wastewater still met the requirements of SNI, although several variations did not comply with the standard. However, when evaluated using international standards, all unfired brick variations produced with cassava wastewater met the specified requirements.